2021
DOI: 10.1111/papt.12342
|View full text |Cite
|
Sign up to set email alerts
|

Depth of experiencing and therapeutic alliance: What predicts outcome for whom in emotion‐focused therapy for trauma?

Abstract: Objective The purpose of this study was to determine the extent to which therapeutic processes – working alliance and depth of experiencing – contributed to outcome. Method Individual differences in these processes were examined at the early and working phases to determine their impact on symptom reduction. An archival data set of N = 42 individuals who underwent emotion‐focused therapy for trauma for childhood maltreatment was used to examine the differential quality of client processes throughout treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Hence, clients were seeing the therapist for the first time in a recording studio. This supports the notion that emotion transformation is based on a strong therapeutic alliance and evolves over time [80,81]. When clients start feeling stronger and more resilient, they start standing up for themselves.…”
Section: Self-protectionsupporting
confidence: 80%
“…Hence, clients were seeing the therapist for the first time in a recording studio. This supports the notion that emotion transformation is based on a strong therapeutic alliance and evolves over time [80,81]. When clients start feeling stronger and more resilient, they start standing up for themselves.…”
Section: Self-protectionsupporting
confidence: 80%
“…Among participants receiving either EFT or client-centered therapy, Pos et al (2017) found that depth of experiencing mediated the impact of emotional arousal on treatment outcome. In EFT for trauma, when clients struggled early in treatment to achieve greater depth of experiencing, depth of experiencing (in the working phase) was the best predictor of treatment outcome (Harrington et al, 2021). Conversely, for clients with an initially poor working alliance, the quality of alliance (in the working phase) was the best predictor of treatment outcome (Harrington et al, 2021).…”
Section: Depth Of Experiencingmentioning
confidence: 99%
“…In EFT for trauma, when clients struggled early in treatment to achieve greater depth of experiencing, depth of experiencing (in the working phase) was the best predictor of treatment outcome (Harrington et al, 2021). Conversely, for clients with an initially poor working alliance, the quality of alliance (in the working phase) was the best predictor of treatment outcome (Harrington et al, 2021). Client experiencing has emerged as another key process predictor of outcome, particularly for clients who struggle to engage with emotion and make meaning.…”
Section: Depth Of Experiencingmentioning
confidence: 99%